Meaning of “Status” in “Whatsapp Applicationas a Form of Persuasive Communication between Individuals - Yunita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to find out the meaning of "Status" in the Wharsapp Application as a form of persuasive communication between individuals among students of the Master of Communication Sciences, in the Moestopo Post-Graduate Program, using new media theory and phenomenological theory and symbolic interactionism. Through the constructivist paradigm, this qualitative approach uses phenomenological methods. Data collection technique by conducting interviews with 10 students of the Post Graduate Program in Communication Sciences, Prof. Dr. Moestopo University (Beragama), Jakarta. The interview was conducted through messanger's Whatsaap app. Techniques for data analysis of phenomenology. The results showed that status is interpreted as a symbolic form of persuasive communication.  Symbols are exchanged as a form of persuasive communication in the form of photos, images, videos, and even emoticons. Through these symbols, individuals feel attracted, and persuaded, and respond to the status, so that the communication process  runs, the uploaded status contains certain information, symbolic expressions of the feelings of informants or related to work, hobbies and in the daily life of informants, and even veiled meanings known only by status uploaders.